PENGEMBANGAN DAN VALIDASI METODE PENETAPAN KADAR ASETAMINOFEN DAN IBUPROFEN DALAM TABLET KOMBINASI DENGAN MENGGUNAKAN FOURIER TRANSFORM INFRARED (FTIR) - Nur Khalida, Farah
The development of analytical methods continuesly conducted along with the development of technology. Acceptance of an analytical method development depends on the results of the validation of the method. Analysis of Fourier Transform Infrared Spectroscopy (FTIR) is an analytical method based on the vibration of atoms of a molecule and are widely used for identification and analysis of functional groups in a compound. The drugs combination of acetaminophen (AST) and ibuprofen (IBU) can produce a potentiating effect in relieving pain, reducing fever, and relieve inflammation. The purpose of this study to develop FTIR analytical methods in determining concentration AST and IBU in combination preparation simultaneously. Standard AST and IBU are respectively mixed with KBr in varied and measured the spectra. The measured spectrum is converted into an absorbance and derivatized forms. Wavenumber that give a clear and distinctive crest of each active ingredient is selected and calculated area under the curve. Once validated, the analytical method is conducted on samples of AST and IBU combination tablet in the market. Acetaminophen has a specific wavenumber range at 3289 ? 3220 cm -1 which contained group N-H stretch; Ibuprofen has the C = O in the range of a specific wavenumber 1847 ?1758 cm -1 which is expected to show peaks typical spectra for quantitative calculation basis levels respectively. The linearity test results showed linearity on acetaminophen concentration from 1.00 ?6.00% w/w and ibuprofen 1.50 ?4.00% w/w; with y = 0.0004 x 0.0004; r = 0.9994; VXO value of 0.0309% and ibuprofen is y = 0.0002x 0,002; r = 0.9992; VXO value of 0.8063%. Recovery of acetaminophen is 99.05 ?99.45% and ibuprofen from 98.74 ?101.90%. Intraday precision on three different days and consecutive interday precision of acetaminophen are 1.83; 1.98; 1.79 and 0.2767% and ibuprofen are 1.52; 1.26; 1.34 and 0.3607%. LOD and LOQ of acetaminophen consecutively are 3.249 × 10 ?5 % w/w and 1.083 × 10 ?4 % w/w; ibuprofen is 6.6652 × 10 ?4 % w/w and 2.2174 × 10 ?3 % w/w. Level determination of samples tablet on the market have met compendial requirements. FTIR can be used to measure the concentration of AST and IBU in drug combinations simultaneously. This method has met the validation.